Specification for piling contract documentation and measurement. (Thomas Telford, 1988)
This document specifies the general requirements for piling work and provides guidance on the documentation of piling contracts generally. Other subjects covered in the book include general requirements for concrete piles and precast reinforced concrete segmental piles.